2005
DOI: 10.1186/1471-2431-5-27
|View full text |Cite
|
Sign up to set email alerts
|

Otitis media in young Aboriginal children from remote communities in Northern and Central Australia: a cross-sectional survey

Abstract: BackgroundMiddle ear disease (otitis media) is common and frequently severe in Australian Aboriginal children. There have not been any recent large-scale surveys using clear definitions and a standardised middle ear assessment. The aim of the study was to determine the prevalence of middle ear disease (otitis media) in a high-risk population of young Aboriginal children from remote communities in Northern and Central Australia.Methods709 Aboriginal children aged 6–30 months living in 29 communities from 4 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
177
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(187 citation statements)
references
References 24 publications
7
177
2
Order By: Relevance
“…Previous studies have highlighted that hearing loss and impediments are more prevalent among Indigenous children (ABS 2006), particularly in more remote communities with poor environmental health conditions (Coates et al 2002;Zubrick et al 2004). Middle ear infection, or otitis media, is a persistent problem in many Indigenous communities and is regarded as the most common cause of hearing impediments among Indigenous children (Morris et al 2005).…”
Section: Hearing and Visionmentioning
confidence: 99%
“…Previous studies have highlighted that hearing loss and impediments are more prevalent among Indigenous children (ABS 2006), particularly in more remote communities with poor environmental health conditions (Coates et al 2002;Zubrick et al 2004). Middle ear infection, or otitis media, is a persistent problem in many Indigenous communities and is regarded as the most common cause of hearing impediments among Indigenous children (Morris et al 2005).…”
Section: Hearing and Visionmentioning
confidence: 99%
“…The levels described among children living in some remote communities in northern and central Australia are such that they would be classified by the WHO as being 'a massive public health problem' requiring 'urgent attention' [163, p.2]. In 2001, nearly all children (91%) aged 6-30 months living in some remote communities in the NT and central Australia had been diagnosed with some form of OM [162]. 17 The report defined endemic trachoma as a prevalence of active trachoma of more than 5% in children aged 5-9 years.…”
Section: Extent Of Ear Disease Among Indigenous Peoplementioning
confidence: 99%
“…Prevalence Exceptionally high levels of ear disease and hearing loss have been reported for many years in many Indigenous communities, particularly in remote areas [158,[160][161][162]. The levels described among children living in some remote communities in northern and central Australia are such that they would be classified by the WHO as being 'a massive public health problem' requiring 'urgent attention' [163, p.2].…”
Section: Extent Of Ear Disease Among Indigenous Peoplementioning
confidence: 99%
“…For example, a survey of young Aboriginal children in Northern and Central Australia found that 91% were affected by otitis media (Morris, Leach, Silberberg, Mellon, Wilson, Hamilton, et al, 2005). Extensive testing of Aboriginal children was also conducted through the Child Health Check Initiative (CHCI) introduced under the Northern Territory Emergency Response (NTER), which found that 30% had ear disease (Australian Institute of Health and Welfare and Department of Health and Ageing, 2009).…”
Section: Prevalence Of Communication Disability In Aboriginal Populatmentioning
confidence: 99%